In the land of a thousand gods : a history of Asia Minor in the ancient world - Marek, Christian, 1950- (Princeton University Press, 2016)
A monumental history of Asia Minor from the Stone Age to the Roman Empire In this critically acclaimed book, Christian Marek masterfully provides the first comprehensive history of Asia Minor from prehistory to the Roman imperial period. Blending rich narrative with in-depth analyses, In the Land of a Thousand Gods shows Asia Minor's shifting orientation between East and West and its role as both a melting pot of nations and a bridge for cultural transmission. Marek employs ancient sources to illuminate civic institutions, urban and rural society, agriculture, trade and money, the influential Greek writers of the Second Sophistic, the notoriously bloody exhibitions of the gladiatorial arena, and more. He draws on the latest research-in fields ranging from demography and economics to architecture and religion-to describe how Asia Minor became a center of culture and wealth in the Roman Empire. A breathtaking work of scholarship, In the Land of a Thousand Gods will become the standard reference book on the subject in English.